Prehospital to emergency department handoff: can team-based reporting improve markers of clinical efficiency in an adult emergency department? - Charles W Hwang; Frederick S Southwick; Brandon R Allen; Christopher L Gross; Corey D Cowgill; Brent A Selph; Jessica M Cowgill; Ziad Saqr (BMJ Open Quality)
Interdisciplinary communication is a critical component of quality patient care. On emergency medical services (EMS) arrival to the emergency department (ED), the pre-existing opportunity-based reporting (OBR) handoff paradigm may result in disjointed, repetitive and incomplete transition of patient care to the ED, adversely impacting patient care. This quality improvement study was conducted at a tertiary care, academic university hospital ED and evaluated the impact of team-based reporting (TBR) during EMS patient handoff in the ED on several markers of clinical efficiency (CE). The standard OBR handoff protocol was compared with the TBR protocol, which brings the patient’s ED care team to bedside shortly after patient arrival, allowing EMS to give a single, synchronous handoff. The use of TBR during prehospital-ED handoffs was associated with statistically and clinically significant improvement across multiple CE quality indicators. A team-based handoff strategy is a low-cost policy intervention that provides meaningful improvements related to CE and quality care.